PENGEMBANGAN SIMULATOR UNTUK PENGENDALIAN REAKTOR DAYA TIPE PWR - Deswandri Deswandri (Pusbindiklat - LIPI, 2009)
The load following operation is a mode of operation, where the power level of nuclear power reactor is adjusted based on the load fluctuation at the electric grid. The changes of power level cause unbalance in the reactor. In order to keep the stability of reactor, it needs a specific control method. Three control methods for the PWR type reactors were developed for that purpose. Each method was tested by a numerical simulation, respectively. Since these methods were tested separately, however, it is difficult to compare the performance of all methods directly using the same initial parameters and various standard power patterns. In this work, we developed the simple simulator to simulate the control methods of PWR during the load following operation. By using the standard daily power patterns, it was showed that the simulator could be used well and all results agree with the previous results of the three control methods above. By using the same initial parameters and power pattern, the simulator could directly show the characteristic, superiority and disadvantage of each control method, respectively.